Impacts Socio-Economiques De La Culture De L’anacarde Dans La Sous-Prefecture D’odienne (Côte d’Ivoire) - Sinan, Adaman; Abou, N’dri Kouame (European Scientific Journal, ESJ, 2016)
Introduced in the Ivorian agriculture from 1960, the farming of cashew tree is now rapidly developing, precisely in the Center and North of the country. Odienné sub-prefecture occupies an important place with an estimated production of 33,006 tons in 2015. This increase in production is the consequence of the price per kilogram which increased from 225 fcfa in 2011 to 350 fcfa. These prices contribute to the improvement of the living conditions of the producers and the schooling of their children. But the development of cashew tree causes conflicts between cattle breeders and producers. These conflicts tend to undermine the social cohesion between communities. The objective of the study is therefore to evaluate the economic and social impacts of the cashew tree farming on producers in Odienné sub-prefecture. The survey has favored the combination of qualitative and quantitative approaches.